2020
DOI: 10.1038/s41598-020-70755-y
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin polymorphisms in Latin American populations

Abstract: were also divided into four groups, group 1 (all 45 AA/AA, AA/CA, CA/CA), group 2 (26 of 42 AA/AG), group 3 (16 of 42 AA/AG and all of 10 AG/CA), and group 4 (all of 25 AG/AG) (Fig. 1C,D). One individual had a rare base substitution at position of − 68 (rs55663121) as a heterozygote (T/C). The genotype of this individual was A/A at rs5471 and rs5472, and it belonged to group 3 of rs5471and group 1 of rs5472. In any case, we determined six rs5471 and rs5472 haplotypes accurately except one subject (heterozygote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…However, these clinical features and anthropometric parameters were not significantly associated with a particular haptoglobin genotype (p > 0.05); we can also note significant differences for bacterial infections and vaso-occlusive crises suggesting that the presence of the "HP 2 " allele is a parameter favoring these clinical manifestations. This observation has also been reported by several authors (Bernard et al, 2021;Ostrowski et al, 1987;Park et al, 2004;Soejima & Koda, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, these clinical features and anthropometric parameters were not significantly associated with a particular haptoglobin genotype (p > 0.05); we can also note significant differences for bacterial infections and vaso-occlusive crises suggesting that the presence of the "HP 2 " allele is a parameter favoring these clinical manifestations. This observation has also been reported by several authors (Bernard et al, 2021;Ostrowski et al, 1987;Park et al, 2004;Soejima & Koda, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…The following authors Dahmani et al (2016) and Doupa et al (2017) also reported equitable transmission of the condition between the two sexes. The study population was relatively young with a median age of 9 years (Al-Saqladi et al, 2012;Bandeira et al, 2014;Costacou et al, 2008;Da Guarda et al, 2020;Eric Kerchberger et al, 2019;Gudjoncik, 2018;Langlois & Delanghe, 1996;Santos et al, 2011;Soejima & Koda, 2020;Zahran et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that haptoglobin possess three phenotypes/proteins, which differ in number, type of chain and their molecular weight: phenotype Hp 1‐2, phenotype Hp 1‐1, and phenotype Hp 2‐2 9 . These proteins are probably not equivalent; indeed, previous studies show that patients with the Hp 2‐2 form would have more vascular complications 10–12 . Moreover, this genotype would have an oxidative action while the genotype Hp 1‐1 has an antioxidant action 13 .…”
Section: Introductionmentioning
confidence: 99%
“…9 These proteins are probably not equivalent; indeed, previous studies show that patients with the Hp 2-2 form would have more vascular complications. [10][11][12] Moreover, this genotype would have an oxidative action while the genotype Hp 1-1 has an antioxidant action. 13 According to Langlois et al 14 the phenotype 2-2 is associated in adults with a significant elevation of serum iron, an increase in the transferrin saturation coefficient, an increase in ferritin followed however by a decrease in the concentration of soluble transferrin and/or transferrin receptors; Several other authors show the influence and impact of haptoglobin genotypes on the iron profile.…”
Section: Introductionmentioning
confidence: 99%